Designing an electronic program for the Assessment of project management in accordance with the methodology (PMBOK) - الكبيسي, صلاح الدين عواد; كمال, مصطفى قيس (Journal of Economics and Administrative Sciences, 2020)
The research aims to design an electronic program that allows users to assess the possibility of different practices for projects management professional according to the PMBOK methodology)) and using the requirements Data mentioned in the "knowledge and experience in project management Evaluation guide" issued by the professional Institute of project management According to the results of this program will be electronic The possible classification of project management in terms of both (proficiency_ perform tasks) as less than the desired level or within or above average in terms of best practices, and finally a number of recommendations to overcome the possible shortcomings. The most important is the need to enrich the service sector of government based on the proposed electronic programs to identify the shortcomings and overcome them as well as the use of standard processes according to the manual of knowledge (PMBOK) because it is comprehensive and covers all areas of knowledge management of the project, which may contribute to the higher project success rate.